Penerapan Akad Salam dalam Transaksi Jual Beli Online: Antara Syariah dan Praktik Bisnis - Cindy Ainurrohmah; Angga Aditya Cahyono; Irfan Tri Lasmana (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2025)
ABSTRACT The salam contract is a contract in Islamic law that allows sellers and buyers to make transactions, where payment is made in advance, while the goods being traded are delivered at a later date. This article examines the application of the salam contract to online buying and selling transactions, both from a sharia perspective and modern business practices. This writing is a literature research sourced from online journals, to examine the basic principles of the salam contract in muamalah fiqh, and relate them to e-commerce transaction mechanisms. The salam contract has great potential to be applied in online buying and selling. However, it has several requirements that need to be considered during its implementation, including: agreement between the parties involved in the transaction, clarity in product specifications, delivery date, and the payment method to be used. The application of the salam contract in accordance with sharia principles with fair and transparent business practice standards in the digital era will have many benefits for buyers and sellers, and can be an alternative solution to support sharia-based transactions on online platforms. Keywords: Application, Salam Agreement, Online Buying and Selling, Sharia.